REORGANIZACIÓN DEL PROCESO CONTABLE A LA EMPRESA ELECTROMECÁNICA ALDAZ & ASOCIADOS DE LA CIUDAD DE LOJA, PERIODO ENERO-MARZO 2016 - ALDAZ PESANTEZ, PIEDAD JESÚS (2016)
The thesis called, REORGANIZATION OF ACCOUNTING PROCESS TO THE COMPANY ELECTROMECANICA ALDAZ & ASSOCIATES OF THE CITY OF LOJA, PERIOD JANUARY-MARCH 2016, was made to comply with one of the pre-opt the title of Engineer in Accounting requirements and Auditing Accountant public Auditor accordance with the provisions of the Regulation of Academic Board of the National University of Loja. Within which the following general objective was raised, Reorganizing the accounting process to the company "ELECTROMECANICA ALDAZ & ASSOCIATES" city of Loja period from January to March 2016. And the following specific objectives, design books and records that allow control operations, Develop a Plan and Manual of Accounts according to the needs of the company, develop the accounting process since the lifting of inventories to financial Statements, Applying financial indicators to determine their operational and financial situation of the company, with the in order to verify the actual situation in which the company is located. That is why start designing a plan and accounts manual geared to the needs of the company, which will facilitate the recording of accounting entries in chronological order in the journal. Then it proceeds to develop the accounting process by System Multiple Account which is the method 5 used in this course, starting with an initial inventory that is physical evidence of materials, tools and assets you have in the period study, and then formulate the respective State Initial Situation in which is reflected in summary form all his possessions, then it gives way to record transactions daily develop in the Daybook in an orderly fashion once are recorded in the same are transferred to the respective Ledger which facilitate the development of Balance, Worksheet and finally the preparation and development of the respective financial statements. For all the above process the respective accounting records primarily as the Daybook, Ledger that are a necessary and important to carry out the process tool was designed, which; the owner and other stakeholders can learn about the economic and financial situation in which the company operates, once obtained the financial statements indicators to the financial situation in order to determine the solvency, liquidity and leverage, to achieve and facilitate applied the timely decisions on their own.